Hemorrhagic stroke in children: A case report - Tanja Dukić Vuković; Mirjana Miksić; Tomaž Šeruga; Janez Ravnik (Acta Medico-Biotechnica, 2022)
Purpose: The purpose of this report is to present a case of hemorrhagic stroke in a child.Case report: We present a 13-year-old child with a hemorrhagic stroke, which resulted from spontaneous  bleeding of congenital arteriovenous malformations in the brain.Conclusion: Although a brain stroke in children is rare, it is an important cause of disability and mortality. Clinical, neurologic, and radiologic examinations are key for the detection and treatment of arteriovenous malformations, which are the most important cause of hemorrhagic stroke in children and may threaten a child's health and life.